The Effect of Problem Based Learning on Students’ Mathematical Problem Solving Skills - Mude, Moh Andra Ramadhan I. H.; Badu, Syamsu Qamar; Irfah, Auli (IKIP Siliwangi, 2025)
This study was motivated by the low mathematical problem-solving skills of students at SMP Negeri 2 Suwawa, which is believed to be caused by the use of the Direct Instruction model that has not effectively supported the development of such skills. This study aimed to examine the effect of implementing the Problem-Based Learning (PBL) model on students’ mathematical problem-solving abilities, particularly on the topic of Systems of Linear Equations in Two Variables (SPLDV). The research employed a quasi-experimental method with a pretest-posttest design with a nonequivalent group. The participants were students of classes VIII-3 and VIII-4 at SMP Negeri 2 Suwawa, selected through cluster random sampling. The instrument used was a test measuring mathematical problem-solving skills based on SPLDV material. The hypothesis was tested using the t-test, which yielded a result of tₕ = 3.767 > tₜ = 2.024, indicating that students taught using the PBL model had significantly higher average problem-solving abilities than those taught using the Direct Instruction model. Additionally, the effect size calculated with Cohen’s d was 1.191, categorized as a high effect. These results suggest that the implementation of Problem-Based Learning significantly enhances students' mathematical problem-solving skills and can serve as an effective alternative to traditional instructional models in mathematics learning.